(untitled) (Vietnam Journal of Community Medicine, 2024)
Aims: - Describe the thickness, the degree of atherosclerosis of the internal thoracic artery, radial artery, right gastroepiplotic artery, and inferior epigastric artery. - Compare the histological characteristics of the internal thoracic artery, radial artery, right gastroepiploic artery and inferior epigastric artery. Methods: Descriptive study of a series of cases, convenient sampling. Each studied artery was cut at 2 locations: 5mm and 15cm from the origin. Arterial segments were processed and stained according to standard procedures of the Department of Pathology, University of Medicine and Pharmacy at HCM city. At each location, arterial samples were stained with H.E. To measure the thickness of vascular wall layers and evaluate pathological lesions in blood vessel walls. Results: The thickness of the media intima of the radial artery (range ranges from 270.68 µm - 308.56 µm) is greater than that of the remaining arteries. The range of change in medial intima thickness in the remaining three arteries is: 79.12 µm - 97.62 µm (internal thoracic artery); 67.34 µm - 79.12 µm (inferior epigastric artery) and 73.89 µm - 83.03 µm (right gastroepiplotic artery). Conclusions: According to histological results, the priority order of arteries used in coronary artery bypass surgery is: internal thoracic artery, radial artery, and right gastroepiplotic artery.